2011
DOI: 10.1002/lary.21928
|View full text |Cite
|
Sign up to set email alerts
|

Development of a test to evaluate olfactory function in a pediatric population

Abstract: Objectives/Hypothesis This study evaluated two versions of a test for olfactory function to determine suitability for use in a pediatric population. Study Design Cross-sectional cohort study. Method In phase 1, 369 children (ages 3–17 years) and 277 adults (parents) were tested. Children began with identification and familiarity judgments to pictures representing target odors and distractors. Odors were administered via a six-item scratch and sniff test. Each answer sheet contained the correct odor source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 13 publications
4
28
0
Order By: Relevance
“…13 In the first study, 369 children (aged 3-17 years) and 277 adults (parents) were tested. In the second study, 50 children (aged 3-4 years) and 43 adults were given a revised version of the test with 8 odors that had been judged to be more representative of the odor source and more familiar to children.…”
mentioning
confidence: 99%
“…13 In the first study, 369 children (aged 3-17 years) and 277 adults (parents) were tested. In the second study, 50 children (aged 3-4 years) and 43 adults were given a revised version of the test with 8 odors that had been judged to be more representative of the odor source and more familiar to children.…”
mentioning
confidence: 99%
“…12,17 The use of common items in the administration of SDCOIT affects its standardized nature, making interpretation of the findings around olfaction more limited. 20 Similarly, the use of known trigeminal nerve stimulants as part of assessment in Roberts and Simcox's two-odor olfactory measure, and in Hagan's case study, limit the conclusions that can be made about the function of the olfactory system for their cohorts. 14,22 The natural history of olfactory dysfunction post-TBI remains to be established in a pediatric cohort, with findings in the included studies limited by cross-sectional study designs and anecdotal reporting of results.…”
Section: Discussionmentioning
confidence: 95%
“…Recent developments in assessing olfaction in children as young as 3 years are encouraging and are the first step in increasing the awareness of assessment of olfactory function. 20,21 Without clinically applicable, ageappropriate assessment measures, the accurate assessment and identification of olfactory deficits in a clinical setting is likely to continue to be under-represented. The use of such measures in future olfactory function research in young children will assist with previously identified issues of ensuring standardized developmentally appropriate assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of whether the test is actually measuring olfactory ability in young children or whether cognitive or language confounds are responsible for their relatively poor performance. Dalton et al observed in their cross‐sectional cohort study that children as young as 3 years of age can perform olfactory testing as they were perfectly capable of understanding the instruction and question of the tests. Nevertheless, we used the Likert scoring system to assess the olfactory function in a high number of patients from 6 to 12 years old showing a good correlation with ARIA severity classification.…”
Section: Discussionmentioning
confidence: 99%